Role of monooxygenases in insecticide resistant anopheles funestus(diptera: culicidae) - Amenya, Dolphine Achieng' (My University, 2007)
The widespread use of pyrethroid insecticides has led to the emergence of significant insecticide resistance in various parts of the world. An unprecedented increase in the number of annual malaria cases reported in Kwazulu Natal, South Africa in 1999 to 2000 was attributed to the re-emergence of pyrethroid-resistant Anopheles funestus Giles. Resistance was metabolic-based with increased monooxygenase (P450) metabolising the pyrethroid insecticides. This emphased the need to understand the molecular mechanisms conferring pyrethroid resistance in An. funestus. The present study aimed to firstly isolate P450 genes in An. funestus and secondly, to identify P450 gene over-expressed in a resistant (FUMOZ-R) strain compared to a susceptible (FANG) strain. A third aim was to construct an An. funestus cDNA library to lay the foundation for future studies on P450 monooxygenses. Degenerate primers based on conserved regions of three An. gambiae P450 families were used to amplify cDNAs from An. funestus. Eleven CYP4, four CYP6 and five CYP9 partial genes were isolated and sequenced. BLAST results revealed that An. funestus P450s have a high sequence similarity to An. gambiae with above 75% identity at the amino acid level. The exception was CYP9J14. The An. gambiae P450 with the closest similarity to CYP9J14 exhibited only 55% identity suggesting a recent duplication event in CYP9J14. Molecular phylogenetic analysis also supported this hypothesis. Intron positions were highly conserved between the two species. Expression studies using blot analysis implicated CYP6P9, an ortholog of CYP6P3 in An. gambiae, as the over-expressed P450. Dot blot analysis revealed a 500-fold expression higher in FUMOZ-R strain compared with FANG strain. Semiquantitative PCR revealed that CYP6P9 was developmentally regulated. Expression was not detected in eggs and was higher in larvae compared to pupae. Quantitative real time PCR showed that CYP6P9 expression was 4.5-fold higher in 3-day old FUMOZ-R males than females and 3.5-fold higher in the 14-day old males than 14- day old females. Statistically, this difference was not significant suggesting that CYP6P9 expression is not sex specific. The An. funestus cDNA library construction in λTriplEx2 vector was successful with a titre of 4.9 x108 pfu/ml and a transformation efficiency of 98%.
Student Number : 0318930A - PhD thesis - School of Animal, Plant and Environmental Studies - Faculty of Science
Keywords: Malaria vector; Insecticide resistance; Monoxygenases; Anopheles funestus